Computer-Assisted Language Learning (CALL) - Seljan, Sanja (Array, 2004)
As computers have become widespread in schools, homes and business, a need for language learning has become urgent and the necessity of computer literacy has become very obvious, language teachers have started to use new technologies as a new pedagogical tool in foreign language teaching. Introduction of new pedagogical tools does not reject, but includes programs and methods of the previous phase, representing inevitable innovation that gains acceptance slowly and unevenly. Multimedia computing, the Internet, and the World Wide Web have provided an incredible boost to Computer Assisted Language Learning (CALL) applications, offering a wide variety of educational, programs, resources, software, journals, organizations, software tutorials including all types of exercises for grammar drills, vocabulary, listening and pronunciation exercises, games, etc. After giving a general picture of CALL development, this article focuses on exploitation of the language resources and learning materials that are accessible on CD-ROMs and on the Internet, presents two CALL projects, and reports experiences in partner universities. In terms of theoretical approach, practice, computer and communication technology, CALL represents a challenge for the teacher and for students as a new medium of exploration.